2019
DOI: 10.1002/cphc.201900051
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Weak Metal−Metal Bonding: Is There a Beryllium‐Beryllium Triple Bond?

Abstract: Metal‐metal triple bonds featuring s‐block element have not been reported until now. Only Be−Be double bonds between have been predicted theoretically based on the intuitive electron donation from four s1 type electron‐donating ligands. Herein, we theoretically predicted a novel species featuring a Be−Be triple bond in the Li6Be2 molecule. The molecule was found to be thermodynamically stable. The presence of the triple bond was confirmed by adaptive natural density partitioning (AdNDP), electron localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
(33 reference statements)
2
19
0
Order By: Relevance
“…We note that Liu et al have interpreted the bonding in the octahedral Be 2 (μ 2 ‐Li) 4 cluster, and others, in terms of a Be=Be double‐π bond and the bonding in Be 2 X 4 Y 2 clusters (X = Li, Na and Y = Li, Na, K) in terms of Be≡Be triple bonds . Calculations and analysis carried out by Rohman et al also support the notion of Be≡Be triple bonds in various systems, including Be 2 X 6 (X = Li, Na), but they found the BeBe bonding to be ultraweak in spite of the very short BeBe distances . Indeed, some systems have been studied both experimentally and computationally, such as the rhombic Be 2 O 2 cluster, which feature very short BeBe distances in the absence of any direct BeBe chemical bonding …”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We note that Liu et al have interpreted the bonding in the octahedral Be 2 (μ 2 ‐Li) 4 cluster, and others, in terms of a Be=Be double‐π bond and the bonding in Be 2 X 4 Y 2 clusters (X = Li, Na and Y = Li, Na, K) in terms of Be≡Be triple bonds . Calculations and analysis carried out by Rohman et al also support the notion of Be≡Be triple bonds in various systems, including Be 2 X 6 (X = Li, Na), but they found the BeBe bonding to be ultraweak in spite of the very short BeBe distances . Indeed, some systems have been studied both experimentally and computationally, such as the rhombic Be 2 O 2 cluster, which feature very short BeBe distances in the absence of any direct BeBe chemical bonding …”
Section: Introductionsupporting
confidence: 54%
“…In spite of the obvious deterrence for experimentalists of the high toxicity of beryllium compounds, a great deal is now known about the organometallic and coordination chemistry of beryllium . Beryllium compounds that have been studied experimentally and especially computationally include various systems that feature BeBe bonding and/or very short BeBe distances . For example, it has been shown for various choices of X, such as a fluorine atom or an appropriate N‐heterocyclic carbene ligand, that certain XBeBeX species feature Be−Be bonds that are both significantly stronger and shorter than the weak and rather long bond in Be 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be also observed that the BeÀ Be distances are around 2 Å, and therefore rather similar to the ones reported previously in the literature [7][8][9][10][11][12][13][14] for different complexes involving Be 2 , including those cases in which the BeÀ Be interaction was found to be significantly strong. However, a detailed analysis of the bonding and the orbitals of the complexes in Figure 1 indicates that the two Be atoms are covalently bonded to the carbon atoms of the two C n H n moieties; but no BeÀ Be bonding interaction is detected.…”
Section: N H N à Be 2 à C N H N (N = 2 4 6 8) Clusterssupporting
confidence: 89%
“…[9] More recently, it was claimed that BeÀ Be double π-bonds were behind the strength of the BeÀ Be interaction in Be 2 (μ 2 -X) 4 (X=Li, Cu, BeF) octahedral clusters, [10] and that BeÀ Be triple bonds could be found in Li 6 Be 2 molecule. [11] In a similar context, it was also showed that the insertion of Be in beryllocene (C 5 H 5 À BeÀ C 5 H 5 ) to yield the corresponding binuclear metallocene (C 5 H 5 À Be 2 À C 5 H 5 ) is rather exothermic (274.9 kJ • mol À 1 ), indicating that the BeÀ Be interaction is strongly stabilizing. [12] Similar results were found when cyclopentadiene was replaced by its P-containing derivative, the phosphole radical (η 5 -C 4 H 4 P * ), [13] and in multimetallocenes.…”
Section: Introductionmentioning
confidence: 91%
“…The Chemistry of Be needs attention due to its toxicity. Therefore, the search for safer Be containing compounds is very essential which is gaining importance both theoretically and experimentally . The first example of transition metal Be dative bond in [(PCy 3 ) 2 Pt–BeCl 2 ] and [(PCy 3 ) 2 Pt–BeCl(CH 3 )] have recently been synthesized which suggest the Lewis acidity of BeCl 2 .…”
Section: Introductionmentioning
confidence: 99%